1997
DOI: 10.1128/mcb.17.9.5033
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mouse Histone Deacetylase 1 as a Growth Factor-Inducible Gene

Abstract: Reversible acetylation of core histones plays an important role in transcriptional regulation, cell cycle progression, and developmental events. The acetylation state of histones is controlled by the activities of acetylating and deacetylating enzymes. By using differential mRNA display, we have identified a mouse histone deacetylase gene, HD1, as an interleukin-2-inducible gene in murine T cells. Sequence alignments revealed that murine HD1 is highly homologous to the yeast RPD3 pleiotropic transcriptional re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
101
0
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 75 publications
6
101
0
1
Order By: Relevance
“…Deconvolution reveals that cln3⌬ cells show roughly equal proportions of G 1 and S phase cells, but no other phases. For each of the other strains, the observed deconvolution results match the defects observed by other techniques (17)(18)(19)(20)(21), such as the known post-S phase delay of cells overexpressing calmodulin [CMD1 (Tet)], which are defective in nuclear division (22), exhibiting a higher proportion of M and M͞G 1 cells in our analysis.…”
Section: Validation Of Expression Deconvolution Analysissupporting
confidence: 75%
“…Deconvolution reveals that cln3⌬ cells show roughly equal proportions of G 1 and S phase cells, but no other phases. For each of the other strains, the observed deconvolution results match the defects observed by other techniques (17)(18)(19)(20)(21), such as the known post-S phase delay of cells overexpressing calmodulin [CMD1 (Tet)], which are defective in nuclear division (22), exhibiting a higher proportion of M and M͞G 1 cells in our analysis.…”
Section: Validation Of Expression Deconvolution Analysissupporting
confidence: 75%
“…The enzyme is not only essential for mouse development but also for normal proliferation of mouse embryos and embryonic stem cells (23). HDAC1 expression has to be tightly regulated since both overexpression and loss of HDAC1 result in severe disturbance of proliferation and cell cycle progression (23,24). Transcription of the murine HDAC1 gene is induced by cooperative phosphorylation and acetylation signals, allowing both growth factor-dependent activation and feedback regulation (25,26).…”
mentioning
confidence: 99%
“…Lanes 1, 3, 6 and 9: 5 mg p120 E4F plus 5 mg myc-HDAC1 plus 5 mg of myc-Gam1; lane 2: 5 mg of myc-Gam1 plus 10 mg of empty vector; lane 4: 5 mg myc-HDAC1 plus 10 mg of empty vector; lane 5: 5 mg myc-HDAC1 plus 5 mg of myc-Gam1 plus 5 mg of empty vector; lane 7: 5 mg p120 E4F plus 10 mg of empty vector; lane 8: 5 mg p120 E4F plus 5 mg myc-HDAC1 plus 5 mg empty vector. Cells were ( 35 S) Met labeled (Amersham) and cellular lysates were immunoprecipitated with anti-LexA antibody (Santa-Cruz) (lane 1), anti-myc antibody (lanes 2 and 3), anti-HDAC1 antibody (Bartl et al, 1997) (lanes 4-6) and anti-HA (lanes 7-9). (b) U2OS cells (1 Â 10 6 ) were transfected with 5 mg of HA-p120 E4F , 5 mg of myc-HDAC1 and 5 mg of myc-Gam1.…”
mentioning
confidence: 99%
“…As shown in Figure 2a, in vitro translated p120 E4F bound to GST- HDAC1. To assess whether the two proteins would also interact in vivo, myc-HDAC1 (Bartl et al, 1997) and HA-p120 E4F (Sandy et al, 2000) were expressed in HeLa cells. Immunoprecipitation with anti-myc followed by immunoblotting with anti-HA demonstrated that HDAC1 and p120 E4F interact (Figure 2b, lane 3).…”
mentioning
confidence: 99%